Recyclable hypervalent-iodine-mediated solid-phase peptide synthesis and cyclic peptide synthesis - Liu, Dan; Guo, Ya-Li; Qu, Jin; Zhang, Chi (Beilstein Journal of Organic Chemistry, 2018)
The system of the hypervalent iodine(III) reagent FPID and (4-MeOC6H4)3P was successfully applied to solid-phase peptide synthesis and cyclic peptide synthesis. Four peptides with biological activities were synthesized through SPPS and the bioactive cyclic heptapeptide pseudostellarin D was obtained via solution-phase peptide synthesis. It is worth noting that FPID can be readily regenerated after the peptide coupling reaction.
Keywords: cyclic peptide; FPID; hypervalent iodine(III) reagent; recyclable; solid-phase peptide synthesis (SPPS)